Consumption, Sustainability and Everyday Life - Hansen, Arve; Bo Nielsen, Kenneth (Consumption and Public Life, 2023)
"In showing how concepts of consumption, sustainability and everyday life have combined and changed over time and in confronting fundamental questions of excess, growth and the ratcheting of demand, this is a book that looks to the future. Individually and in combination the chapters underscore the importance and relevance of social science and the power of careful research and scholarship. The result is a fitting tribute to Hal Wilhite, a pioneer in this field." - Elizabeth Shove, Distinguished Professor of Sociology, Lancaster University, UK This open access book seeks to understand why we consume as we do, how consumption changes, and why we keep consuming more and more, despite the visible damage we are doing to the planet. The chapters cover both the stubbornness of unsustainable consumption patterns in affluent societies and the drivers of rapidly increasing consumption in emerging economies. They focus on consumption patterns with the largest environmental footprints, including energy, housing, and mobility and engage in sophisticated ways with the theoretical frontiers of the field of consumption research, in particular on the 'practice turn' that has come to dominate the field in recent decades. This book maps out what we know about consumption, questions what we take for granted, and points us in new directions for better understanding-and changing-unsustainable consumption patterns. Arve Hansen is a researcher at Centre for Development and the Environment, University of Oslo, Norway, where he leads the centre's research group on consumption and energy and the Norwegian Network for Asian Studies. His research focuses on sustainable consumption in Norway and Southeast Asia, with particular focus on the relationship between everyday practices and economic systems. Kenneth Bo Nielsen is Associate Professor at the Department of Social Anthropology at the University of Oslo, Norway, and leader ofthe Norwegian Network for Asian Studies. His research is focused on political economy, land politics, dispossession, and social movements, with a particular emphasis on India where he has worked for two decades.